Odpowiedzi

2010-04-08T17:24:05+02:00
A)3/4x=-4/9 /: 3/4
x = (-4/9) : 3/4
x = (-4/9) x 4/3
x = -16/27

b)-3x=7 /: (-3)
x = -7/3
x = -2 i 1/3

c)1,2x=4,8 /: 1,2
x = 4

d)-3/5x=-5 /: (-3/5)
x = (-5) x (-5/3)
x = 25/3
x = 8 i 1/3

e)0,1x=-7 /: 0,1
x = (-7) : 1/10
x = (-7) x 10
x = -70

f)-3x=2x-10
-3x - 2x = -10
-5x = -10 /: (-5)
x = 2

g)2x-2=7-x
2x + x = 7 + 2
3x = 9 /: 3
x = 3

h)10=4-2x
4 - 2x = 10
-2x = 10 - 4
-2x = 6 /: (-2)
x = -3

i)-(2x-1)=4
-2x + 1 = 4
-2x = 4 - 1
-2x = 3 /: (-2)
x = -3/2
x = -1 i 1/2